صعوبات البحث والتكوين في تخصص الدعوة والإعلام بمعاهد العلوم الإسلامية - قادري, محمد الصديق (جامعة الوادي - University of Eloued, 2018)
تتمحور هذا الورقة البحثية حول الحديث عن الصعوبات التي تصادف الطالب والباحث في تخصص الدعوة والإعلام، وذلك من خلال تقييم تجربتي كطالب ثم باحث ثم مدرس في هذا المجال، وقد قُسمت هذه الورقة إلى مقدمة ومطلبين، المقدمة وكان فيها الحديث عن أهمية تخصص الإعلام والدعوة، أما المطلب الأول فكان فيه التعريف بهذا التخصص عموما ثم في معاهد العلوم الإسلامية، أما المطلب الثاني فكان للحديث عن صعوبات التكوين و البحث العلمي ثم كانت الخاتمة بتوصيات لتطوير هذا التخصصThis paper focuses on the difficulties encountered by the student and the researcher in the field of advocacy and information, by evaluating my experience as a student and then as a researcher and then as a teacher in this area. This paper has been divided into an introduction and two preamble, where the talk about the importance of media and advocacy, In which the definition of this specialization in general and then in the Institute of Islamic Sciences in the valley, the second was to talk about the difficulties of training and scientific research and then the conclusion and recommendations for the development of this specialization.
مقال
Keywords: الصعوبات ،البحث، التكوين،الدعوة،الإعلام; Difficulties, research, formation, advocacy, media